EFFECTIVENESS OF PREEMPTIVE ANALGESIA IBUPROFEN 10 MG / KGBB PER ORAL FOR POSTOPERATIVE PAIN MANAGEMENT IN CHILDREN UNDERGOING MASS CIRCUMCISION - Muhammad Jalaluddin Assuyuthi Chalil (Universitas Muhammadiyah Sumatera Utara, 2019)
Management of post-mass circumcision pain is often overlooked and not optimal because the administration of analgesia will be given when circumcision is complete. This study aims to determine the effectiveness of oral 10 mg / KGBB ibuprofen as preemptive analgesia for the management of post mass circumcision pain. After obtaining permission from the ethics commission of the FK UMSU clinical research, a prospective double-blind randomized controlled clinical trial was conducted on 28 children in consecutive sampling who met the inclusion and exclusion criteria. Samples were randomized into 2 groups, A was given ibuprofen 10 mg/kg BW orally 1 hour before incision and B was given ibuprofen 10 mg/kg BW orally at the time immediately after the circumcision was completed. Pain scale measurements were performed using FPR-S (Faces Pain Scale-Revised) at the 1st, 2nd, 4th, 6th and 8th postoperative hours. Monitoring of the 1st to 4th hours is carried out at the location of the activity, while the 6th to 8th hours are carried out by telephone. There was a significant decrease in pain scale at the 1st hour (p = 0.031) in group A. At the second to eighth-hour monitoring, the effectiveness of the two methods was the same. In conclusion, the method of preemptive analgesia is effective for the management of post-mass circumcision pain.Keywords: preemptive analgesia, post-circumcision pain